2017
DOI: 10.1111/tbed.12679
|View full text |Cite
|
Sign up to set email alerts
|

Equine hepacivirus persistent infection in a horse with chronic wasting

Abstract: Equine hepacivirus is the closest homologue of hepatitis C virus. Limited data on the clinical features of this infection are available. We report the identification of a horse with high-titre viremia by equine hepacivirus. Over a 15-month follow-up, the clinical signs and the viremic status persisted, suggesting a chronic evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…In contrast, EqHV and EqPV‐H are hepatotropic and have frequently been detected in cases of mild or subclinical hepatitis 2,20,21 . EqHV infection has only been reported in three cases of severe clinical liver disease 22‐24 . EqHV was associated with chronic, severe hepatopathy in two cases 23,24 and detected in one case of acute severe hepatitis 22 .…”
Section: Equine Acute Hepatitismentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, EqHV and EqPV‐H are hepatotropic and have frequently been detected in cases of mild or subclinical hepatitis 2,20,21 . EqHV infection has only been reported in three cases of severe clinical liver disease 22‐24 . EqHV was associated with chronic, severe hepatopathy in two cases 23,24 and detected in one case of acute severe hepatitis 22 .…”
Section: Equine Acute Hepatitismentioning
confidence: 99%
“…In contrast, EqHV and EqPV-H are hepatotropic and have frequently been detected in cases of mild or subclinical hepatitis [2; 20; 21]. EqHV infection has only been reported in three cases of severe clinical liver disease [22][23][24].…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Until now, whether EqHV infection is associated with liver disease remains unclear. However, it has been reported that horses infected with EqHV could developed severe hepatitis and chronic wasting[ 9 , 10 ]. EPgV and TDAV were first discovered in horses in the USA in 2013[ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to equine hepacivirus (EqHeV), which has been classified into different subtypes by multi‐target genome analysis (Elia et al., 2017; Lu, Ou, Sun, et al, 2019; Pronost et al., 2017), BovHepV also shows a marked genetic diversity with geographic‐derived patterns observed in the circulating strains (Lu et al., 2018). By applying the criteria adopted for HCV genotyping and subtyping to the available complete BovHepV genomes, it has been proposed to classify BovHepV strains as a single genotype (genotype 1) and four different subtypes (A to D).…”
Section: Introductionmentioning
confidence: 99%